Design thinking in the scope of strategic and collaborative design - Grácio, Helena Luz (2019)
The aim of this paper is to present a reflection from a design perspective, regarding the importance of collaborative work among higher education students, in different cultures and context realities, using as a starting point a design thinking workshop. The goals of the workshop were, by introducing the principles of design thinking to a focus group of university students, in Finland, implement and develop the ability to experiment the design thinking process, and to realize how the interaction of different perspectives can lead to innovative solutions, as to the promotion of interdisciplinary work. Design thinking is a flexible methodology, which can be used in any work field, since it has valuable elements, such as iterating frequently based on continuous feedback from all the intervenient. Through rapid low-resolution prototyping, ideas are continuously tested with the potential users. “Fail early in order to succeed sooner” is the design thinking principle that helps to maximize learning and insights, crucial for human centred innovation. Collaborative work in a small groups scenario map leads to the discussion of solutions, and to the innovation that emerges from the different perspectives given by each person. Our main goal was to find business opportunities that emerge from underestimated issues from everyday life, but also to understand that exploring, understanding, and prioritizing areas can be crucial to ideating solutions.